Florestas brancas do semiárido nordestino: desmatamento e desertificação no cariri paraibano. - Travassos, Ibrahim Soares (2012)
According to the UN, desertification is a type of degradation that occurs in areas, arid, semiarid and dry sub-humid, resulting from climate change and human activities. In Brazil, the Northeast semiarid region has primacy in the development of this phenomenon. Thereby was carried out in this work a review of the historical processes of occupation of the region, analysis of the secular public policies to combat drought and times (cycles) developed in economic Cariri. Trying to understand desertification as a result of the relationships that historically [re]produce this space. The methodology relied on the research literature, consultations with government statistical data on the extraction activities and field work in order to conduct investigations and collect soil samples that have suffered various types of use to know whether there were changes in normal patterns of fertility originally found. The results show that since the arrival of the colonizer caririseiras landscapes have been greatly altered. Highlighting the historical and cultural importance of using vegetation as an alternative economic and energy by the population. In private in the cities studied (São João do Tigre, São Sebastião do Umbuzeiro e Camalaú), the trade of wood earns state and interstate boundary, especially for large quantities of wood that are exported to the city of Pernambuco constituting the Polo Geseiro. Since the experimental part of the research showed that intensive deforestation, affect the vegetation, also causes changes in this feature, especially in the chemical elements phosphorus (P), potassium (K) and stuff organic which are the main elements present in soils of the Brazilian semiarid region. In summary form, this type of economic practice that occurs in the cities studied and in all that occurs in semiarid northeastern shaky foundations. In this case, the increase endangers the whole area, which by natural conditions prevailing tendency to exhibit the phenomenon of desertification in the medium term that may further aggravate thesituation in the region of land.